(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Abstract. This article explores adolescence from a psychological perspective through J. D. Salinger’s novel The Catcher in the Rye. Adolescence is described as an important stage of human development, often accompanied by emotional instability, confusion, and the search for personal identity. The study focuses on how these psychological characteristics are reflected in the main character, Holden Caulfield. The article also examines simple yet effective narrative tools such as informal language, inner monologue, symbolism, and first-person narration, which help to present the adolescent mind in a realistic way. The analysis proves that the novel offers a clear and convincing psychological picture of adolescent experience, including loneliness, trauma, and the desire for sincerity.